2021
DOI: 10.1111/jbfa.12528
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender, and risk‐taking: Evidence from the S&P 1500 executives and market‐based measures of firm risk

Abstract: This paper contributes to the literature by examining whether the age and gender of the firm's top executives influence market‐based measures of firm risk. Using data on the S&P 1500 firms, we document that chief executive officer (CEO) and chief financial officer (CFO) age and gender have a direct effect on market‐based firm risk measures in addition to the indirect influence they may have through corporate policy choices. Specifically, we find that firms led by older CEOs and CFOs have less volatile stock re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 99 publications
(136 reference statements)
0
18
0
Order By: Relevance
“…It is calculated as the square root of 252 multiplied by the standard deviation of daily stock returns (Bernile et al , 2018). This operationalization of market-based firm risk is considered as the total risk (Peltomaki et al , 2021) and has been used extensively in the firm risk literature (Peltomaki et al , 2021; Bhat et al , 2020; Bernile et al , 2018). We use the natural logarithm of σRet, Ln(σRet), in model estimations to reduce skewness and ease interpretation (Low, 2009; Sias, 1996).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is calculated as the square root of 252 multiplied by the standard deviation of daily stock returns (Bernile et al , 2018). This operationalization of market-based firm risk is considered as the total risk (Peltomaki et al , 2021) and has been used extensively in the firm risk literature (Peltomaki et al , 2021; Bhat et al , 2020; Bernile et al , 2018). We use the natural logarithm of σRet, Ln(σRet), in model estimations to reduce skewness and ease interpretation (Low, 2009; Sias, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…In sum, despite the common belief that managerial skills improve with age, the flip side of the coin is that the deterioration of cognitive skills offsets the positive effect of age on gaining managerial skills (von den Driesch et al, 2015). Regarding the age of CEO in particular, there is some evidence suggesting that CEO age is negatively associated with volatility of stock returns and operating leverage (Peltomaki et al, 2021;Serfling, 2014). These findings suggest that age is an attribute that increases managers' risk averseness and hinders risk-taking motivation even further.…”
Section: 2mentioning
confidence: 98%
See 1 more Smart Citation
“…Gender differences in behavior have been extensively studied in fields such as psychology and even experimental economics ( Peltomäki et al, 2021 ). Research prior to the 1980s considered that women possess certain characteristics, such as being more conformist and less aggressive, that lead them to take fewer risks.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Indeed, we have only found seven previous works in this regard. Three of these studies analyze the U.S. market, and, while one finds that the relationship is negative and significant ( Perryman et al, 2016 ), two consider that there is no relationship between the two variables ( Sila et al, 2016 ; Peltomäki et al, 2021 ). Three other studies were conducted on companies in the United Kingdom ( Nadeem et al, 2019 ), Norway ( Yang et al, 2019 ), and Vietnam ( Van Vo et al, 2021 ), and the presence of women on the boards of directors was found to be negatively and significantly related to systematic risk.…”
Section: Introductionmentioning
confidence: 99%